2009
DOI: 10.1007/s12011-009-8341-x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Mercury in Ovaries of Mice After the Application of Skin-lightening Creams

Abstract: Skin-lightening creams are being increasingly used by women in particular, worldwide in an attempt to whiten their skin. Men and older people use these creams to remove age spots or other pigmentation disorders. Several studies have reported the presence of high mercury levels in skin-lightening cream. Women, especially pregnant and nursing mothers, who use these creams are at risk of mercury toxicity because long-term exposure can cause permanent neurological damage, nephrological disorders, fertility problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…Moreover, oocytes exposed at earlier stages of maturation, with no or immature ZP and fewer follicular cells, could be more vulnerable to DNA damage induced by C e O 2 ENPs. Given the impact demonstrated by the C e O 2 ENPs on the reproduction of the aquatic organisms [23,24] and the hypothesis of a possible bioaccumulation in ovary [33], we plan to study interactions between C e O 2 ENPs and oocytes. In vitro studies will help us to determine the mechanisms of ENP interactions under controlled conditions that represent in vivo situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, oocytes exposed at earlier stages of maturation, with no or immature ZP and fewer follicular cells, could be more vulnerable to DNA damage induced by C e O 2 ENPs. Given the impact demonstrated by the C e O 2 ENPs on the reproduction of the aquatic organisms [23,24] and the hypothesis of a possible bioaccumulation in ovary [33], we plan to study interactions between C e O 2 ENPs and oocytes. In vitro studies will help us to determine the mechanisms of ENP interactions under controlled conditions that represent in vivo situations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mercury can accumulate after application of skin-lightening creams [33]. However, the biodistribution of ENPs in ovaries is unknown [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that exposure to sodium arsenite (0.4 ppm) via drinking water decreased ovarian weight and healthy follicle numbers and increased atresia in rats (Chattopadhyay and Ghosh 2010). Another study showed that dermal exposure to creams that contain high Hg levels caused significant accumulation of Hg in mouse ovaries (87.79 ± 26.20 ng/g and 3,515.61 ± 1,099.78 ng/g), which could alter reproductive outcomes (Al-Saleh et al 2009). …”
Section: Heavy Metalsmentioning
confidence: 99%
“…However, sporadic incidences of Cd and Hg contamination (over 0.5 ppm and 0.05 ppm, respectively) have been reported in particular parts of Taiwan farmland owing to the industrial waste mismanagement [32]. The bulk of literature also warns against the cumulative effects of prolonged heavy metal exposure; regular consumption of rice by local populations might pose potential health problems [1][2][3].…”
Section: Effect Of Heavy Metals On the Fruit Body Growthmentioning
confidence: 99%
“…Heavy metal contamination in soils and plants at polluted sites including heavy industries, metal mining, smelting, and untreated wastewater irrigation areas is commonly found in developing countries [1][2][3]. These heavy metals accumulate mostly in waters and soils, and their action is long-lasting.…”
Section: Introductionmentioning
confidence: 99%